Records Committee review for rare bird sighting for Eskimo Curlew at Davenport in 1901 - Iowa Ornithologists' Union Records Committeeet al (1950)
Records Committee review for Eskimo Curlew at Davenport in Scott County, IA on May 3, 1901. Includes a record review document with votes and the original sighting record found in the publication Specimen of the Eskimo Curlew for Iowa discovered in Iowa Bird Life 20:26 by James Hodges and captured by M. Abbot Frazar. Epson - sheet feed